Social control in transmission of Latin literature - Moniz, Fábio Frohwein de Salles (Revista de Letras, 2015)
This article intends to point out aspects of the bibliographic censorship in the transmission of Latin literature, minimally understood as a set of mechanic and intellectual proceedings at the edition of books aiming at reading orientation and social control. As corpus from our deliberations, we have selected the satire ix, for it is one of Juvenal’s most censored poems within the literary tradition. Primarily, we shall investigate and understand this work, identifying framework elements from the satirical gender and from the juvenalian aesthetics. Later, we may observe questions related to the transmission of the text from Juvenal, chiefly devoting ourselves to the purges in some modern editions from his satires. Regarding the notion of social control, we based ourselves on the thoughts of Émile Durkheim and Michel Foucault, by using newer approaches over the subject, suggested by Marcos César Alvarez (2004) in his article “Controle social: notas em torno de uma noção polêmica”.